Preferensi Mahasiswa FMIPA Dan FT UNP Terhadap Rumah Kos dengan Menggunakan Analisis Konjoin - Dini, Rahmi; Subhan, Muhammad (UNIVERSITAS NEGERI PADANG, 2024)
Out-of-town college students definitely need a place to live. Looking at the boarding house that will be lived in can help determine the right choice for students. This study aims to identify factors that influence student preferences in choosing boarding houses. This research is a survey research using primary data collected directly from students of the Faculty of Mathematics and Natural Sciences and the Faculty of Engineering, Padang State University using questionnaires. Data analysis techniques in this study use conjoint analysis techniques. The steps used are problem formulation, structuring stimuli, forming input data, selection of conjoint analysis procedures, interpretation of results. Based on the data analysis that has been done, the preferred combination of students of the Faculty of Mathematics and Natural Sciences and the Faculty of Engineering, Padang State University in choosing a boarding house is a rental price of Rp. 250,000 – Rp. 550,000, with a distance of less than 1 km from the campus, there are cleaning managers and boarding house guards, boarding houses that have rooms with good air circulation, there are windows, comfortableand clean. Has complete facilities, with 1 occupant per room.